Concomitant Infection with Leishmania donovani and L. major in Single Ulcers of Cutaneous Leishmaniasis Patients from Sudan - Babiker, A. M. (Hindawi Publishing Corporation, 2014)
In Sudan human leishmaniasis occurs in different clinical forms, that is, visceral (VL), cutaneous (CL), mucocutaneous (ML), and post-kala-azar dermal leishmaniasis (PKDL). Clinical samples from 69 Sudanese patients with different clinical manifestations were subjected to a PCR targeting the cytochrome oxidase II (COII) gene for Leishmania species identification. Mixed infections were suspected due to multiple overlapping peaks presented in some sequences of the COII amplicons. Cloning these amplicons and alignment of sequences from randomly selected clones confirmed the presence of two different Leishmania species, L. donovani and L. major, in three out of five CL patients. Findings were further confirmed by cloning the ITS gene. Regarding other samples no significant genetic variations were found in patients with VL (62 patients), PKDL (one patient), or ML (one patient). The sequences clustered in a single homogeneous group within L. donovani genetic group, with the exception of one sequence clustering with L. infantum genetic group. Findings of this study open discussion on the synergetic/antagonistic interaction between divergent Leishmania species both in mammalian and vector hosts, their clinical implications with respect to parasite fitness and response to treatment, and the route of transmission with respect to vector distribution and or adaptation.